Analisis Sentimen Pengguna Terhadap Aplikasi Tripadvisor Sebagai Media Informasi Pariwisata - Sanjaya, I Gede Wahyu; Ananda, I Nyoman; Agung, I Gusti Ngurah Pertu (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2026)
TripAdvisor is a widely used digital application for tourists to access information on destinations, accommodations, and travel experiences. User reviews on the Google Play Store reflect direct perceptions of the application, making them a valuable source for evaluating user satisfaction. This study analyzes 493 tourism-related reviews using a text mining approach, including text preprocessing and sentiment classification. The results show a dominance of positive sentiment, primarily related to ease of use, completeness of information, and the effectiveness of search features. Negative sentiment appears less frequently and is mainly associated with account issues, transactions, and refund processes. These findings indicate that user satisfaction is more influenced by the quality of service and application features than by the tourism destinations themselves. The study provides insights for application developers and offers a systematic understanding of tourist perceptions toward digital tourism applications.